2018
DOI: 10.1186/s13034-018-0247-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of depressive symptoms among sexually abused children in Kenya

Abstract: BackgroundChildren who experience sexual abuse undergo various negative psychosocial outcomes such as depressive symptoms. Unfortunately, not many studies have been conducted on the incidence of depressive symptoms among sexually abused children in Kenya. This study sought to ascertain the incidence of depressive symptoms among children who have experienced sexual abuse in Kenya.MethodsThis was a longitudinal study design. It was conducted at Kenyatta National Teaching and Referral Hospital and Nairobi Women’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Depressive symptomology appeared to vary between studies. Four of the five studies measuring this outcome [20][21][22]25] showed similar patterns of symptoms decreasing over time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Depressive symptomology appeared to vary between studies. Four of the five studies measuring this outcome [20][21][22]25] showed similar patterns of symptoms decreasing over time.…”
Section: Discussionmentioning
confidence: 99%
“…Mouilso et al [23] and Herbert et al [21] scored three stars. Elklit et al [19], Feiring et al [20], Mutavi et al 2017 [24], Mutavi et al 2018 [25], and Oshodi et al [26] scored four stars. Darves-Bornoz et al [18], Rothbaum et al [27] and Khadr et al [22] scored five stars.…”
Section: Quality Assessmentmentioning
confidence: 98%
See 3 more Smart Citations